Diagnoza kryzysu kultury i edukacji = Diagnosis of crisis in culture and education - Szołtysek, Adolf E. (Zielona Góra: Uniwersytet Zielonogórski)
In the treatise the reason for crisis in Polish culture and education has been considered, which was not essentially different from the reason for crisis in European culture and education. The diagnosis has been made in the form of ten main thesis supported by reasoned argument.
Keywords: kultura; edukacja; kryzys; Polska; Europa